The Approaches to the Development of the Identity of Catholic Education of Schools under the Roman Catholic Diocese of Nakhon Sawan. - Aeangpasuk, Sirikul; Thongkhamphong, Sunet (Saengtham College Journal, 2022)
The purpose of the research seemed to investigate the conditions, problems and approaches to the development of the identity of Catholic education of schools under the Roman Catholic Diocese of Nakhon Sawan. The population of the research was 125 signatories acting on behalf of the licensee and managers, school directors, deputy directors for chaplaincy, and Catholic teachers of 7 schools. The data source was 13 experts.The research instruments were questionnaires and interviews. The collected data were analyzed by frequency, percentages, standard deviation, and content analysis. The findings of the research indicated that; as a whole, the conditions of the approaches to the development of the identity of Catholic education of schools under the Roman Catholic Diocese of Nakhon Sawan seemed to be at the high level. The aspect that had the highest level of the management was finance and budgeting. In terms of the problems of the approaches to the development of the identity of Catholic education of schools under the Roman Catholic Diocese of Nakhon Sawan, it was found that aspect the problems were most found was giving monks, priests and priestesses no chance to participate in educational management, including allocating a low budget for governance. The approaches to the development of the identity of Catholic education of schools under the Roman Catholic Diocese of Nakhon Sawan that the experts most frequently recommended were exploring reality in school in the class of Christianity, including doctrines and ethics from the academic department, and adding these subjects to elective courses. In terms of the approaches to the development of the identity of Catholic education of schools under the Roman Catholic Diocese of Nakhon Sawan, it can be said that the schools should develop a system of chaplaincy affecting virtues and desirable values of learners of Catholic schools. In addition, the schools should focus on the approaches to budget development to show the effectiveness of Catholic schools and the identity of Catholic education.